Study of Risk Management Implementation in Hospital X, Denpasar City, Bali Province - Ni Nengah, Sarikumpul; Ida Ayu Putu Sri Widnyani; Gede Wirata (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Various variables, both external and internal, can directly or indirectly hinder the achievement of organizational goals and objectives. Therefore, it is necessary to implement integrated risk management in every decision making, preparation and implementation of programs and activities. The purpose of this study was to determine and analyze the implementation of risk management policies, factors that hinder policy implementation, and solutions to overcome inhibiting factors in the implementation of risk management policies at X Hospital, Denpasar City, Bali Province. This study used a descriptive qualitative research method. The results showed that the implementation of risk management policies at X Hospital, Denpasar City, which included; (1) Communication: communication media is still conventional, while the delivery of one-way information from superiors to subordinates is still long (2) Resources: there is no clear budget line item that mentions risk management (3) Disposition: risk management has not become a culture that requires high commitment (4) Bureaucratic Structure: already in accordance with hospital work procedures. In addition, this study also found risk management implementation strategies, namely; (1) modernization of communication media and continuous socialization of risk management (2) special budget planning for risk management (3) maximizing rewards and punishments for all parties (4) Periodically review the risk management framework based on risk reports and progress of plans and policy implementation. This research is hoped to provide information and input for stakeholders in the region on the implementation of risk management policies.